Jet flipping and scouring below a sluice gate - Lim, Bi Shi. (2013)
The sediment bed downstream of hydraulic structures is often susceptible to an intense local bed degradation or scour. In the present study, the scour characteristics and its associated jet flipping phenomenon caused by a two-dimensional submerged wall jet issuing from a sluice opening are investigated. Experiments were conducted under various tailwater depths, with and without an apron.